Study of effects of silver incorporation on electrical and optical properties of TCO thin films : Luận văn ThS. Công nghệ nano (Chuyên ngành đào tạo thí điểm) - Tran, Thi Ngoc Lan (2019)
Ag-augmented niobium-doped titanium oxide (TNO) and Ag-doped delafossite CuAlxOy thin films were deposited by co-sputtering techniques. The electrical properties were carried out on a 4-point prober. The optical properties were characterized on an UV-VIS spectrometer. The results of TNO thin films indicated that when the Ag concentration increases the resistivity decreases from 2.6x Ω.cm to 3.7x Ω.cm, accompagned with good optical transmittances, higher than 60% in the visible range. The results on CuAlxOy doped Ag thin films showed that CuAlxOy doped Ag they can be hardly applied for transparent conductive layers. However, these films exhibited relatively high temperature coefficient of resistance of about 3%/K, thus being suitable for applications in microbolometers.